Commodities for every portfolio : - Balarie, Emanuel (Wiley, 2007)
As stock market investing becomes increasingly hard to squeeze profits from, savvy investors are finding commodities to be the perfect vehicle for maintaining portfolio performance. Commodities for Every Portfolio shows commodities newcomers how to ease into this straightforward market, which strategies are best (and which to steer clear of!) and much, much more. Investors and traders get easy-to-follow techniques, strategies, and methods, with individual chapters showing how to invest in commodities through stocks, mutual funds, ETFs, and futures. High-performing companies and index-based funds are listed by name, with specific information on how and why they succeed; hard-to-find informational resources are also provided.